USING ONLINE AND OFFLINE RESOURCES IN LANGUAGE LEARNING (Ustozlar uchun, 2026)
This article examines the role of both online and offline resources in language learning and their impact on learners’ success. It analyzes how digital tools and traditional methods complement each other in developing language skills such as speaking, listening, reading, and writing. The study highlights the advantages and disadvantages of each approach and emphasizes the importance of combining them effectively. It also explores how modern learners can benefit from platforms such as Duolingo, YouTube, and Quizlet alongside textbooks and classroom interaction. The article concludes that a balanced use of both online and offline resources leads to more effective and sustainable language acquisition.